The association between dispositional mindfulness and glycemic control in type 1 diabetes during early adulthood: Differences by age and adverse childhood experiences. Issue 4 (16th March 2020) - Nagel, Kathryn E.; Dearth‐Wesley, Tracy; Herman, Allison N.; Smith, Hannah G.; Gandica, Rachelle G.; Golden, Lauren H.; Weil, Henry F. C.; Whitaker, Robert C.
Abstract: Background: The study objective was to determine whether higher levels of dispositional mindfulness were associated with lower HbA1c levels among young adults with type 1 diabetes (T1D) and whether this association differed by age or exposure to adverse childhood experiences (ACEs). Methods: An online cross‐sectional survey, called T1 Flourish, was completed in 2017 by 423 of 743 (56.9%) young adults (19‐31 years) with T1D receiving outpatient care at a diabetes specialty clinic in New York City. HbA1c levels were abstracted from medical records. Respondents were categorized by age, high and low dispositional mindfulness (median split on Cognitive and Affective Mindfulness Scale‐Revised), and exposure to any of 10 ACEs. Results: Respondents had a mean (SD) HbA1c of 64 (18) mmol/mol [8.0 (1.7)%]; 59.3% were female and 69.4% were non‐Hispanic white. The covariate‐adjusted association between dispositional mindfulness and HbA1c differed by age group and ACEs. Among 27‐ to 31‐year‐olds, those with high mindfulness had HbA1c levels that were 8 mmol/mol [0.7%] lower (95% confidence interval, 2‐13 mmol/mol [0.2‐1.2%]) than those with low mindfulness, and this association tended to be stronger in those with ≥1 ACEs. Weaker, non‐significant associations in the same direction occurred in 23‐ to 26‐year‐olds. Among 19‐ to 22‐year‐olds, those with high mindfulness and no ACEs tended to have higher HbA1c levels. Conclusions: In young adults with T1D, higher mindfulness was significantly associated with lower HbA1c only among 27‐ to 31‐year‐olds. In early adulthood, the impact of mindfulness‐based interventions on glycemic control may vary by age and childhood trauma history.